(untitled) (Research, Society and Development, 2021)
The electronic legal process (PJe) was an aspiration of long years and was instituted by resolution of the National Council of Justice (CNJ). The bureaucratization of the judicial process has been discussed for years and aims to provide greater and better access to justice for the right operator, as well as for the poorest population who were far from the information relevant to the most popular causes. In Paraíba, the PJe was implemented gradually. Currently, based on data from the Paraíba Court of Justice (TJPB), the digital collection is in 730,000 cases, surpassing the physical collection, expressed in 7,000. The present study also expresses the status of the collection of processes in the civil forum of João Pessoa, indicating the active physical processes and the files downloaded and not yet migrated to electronic media, demonstrating the importance of implementing the PJe. Furthermore, several authors refer to the social importance of this implantation, providing expeditiousness to justice, practicality to the operator of the law and social justice due to the opportunity of access to those who previously did not have it: the most needy population.